(untitled) (Research, Society and Development, 2023)
The venom of bees of the genus Appis, called Apitoxin, is a complex of bioactive substances, which has shown several benefits and applications in terms of biological activities. Among these bioactive substances is melittin, which corresponds to 50% of the total dry weight of the venom, being the most active toxin in the complex. Literature strongly applies to melittin a hemolytic activity, anti-inflammatory, antifungal, antibacterial and antitumor action. Also apamin, considered the smallest known neurotoxin, acts on the postsynaptic membranes of the central and peripheral nervous system, blocking the transmission of certain inhibitory impulses. Both substances demonstrated biological activities with potential for application in health, so the present work aimed to gather previously published studies and present the discussions and results obtained regarding the research of these two substances.